Pemanfaatan Aset Nagari di Nagari Tanjuang Bonai Kabupaten Tanah Datar - Pratiwi, Helga; Malau, Hasbullah (Lembaga Yasin AlSys, 2024)
Nagari Government is the administration of government affairs and the interests of the Nagari people in the system of Government of the Unitary State of the Republic of Indonesia. Wali Nagari is the administrator of the government, while BAMUS (Consultative Body) is the supervisory agency. The research departs from the management and utilization of assets in the Tanjuang Bonai village which has not been maximized, there is no income or deficit for the nagari originating from the management and utilization of the nagari assets in the Tanjuang Bonai Nagari, Tanah Datar Regency and the unclear management of the Tanjuang Bonai Nagari assets, some are managed community and some are managed by the nagari. This study aims to describe the asset management of Nagari in Nagari Tanjuang Bonai, Tanah Datar Regency, to describe the utilization of Nagari assets in Nagari Tanjuang Bonai, Tanah Datar Regency. This research is a qualitative research using descriptive methods and this research was carried out in Nagari Tanjung Bonai, Tanah Datar Regency and to test the validity of the data the researchers used source triangulation techniques. The results of the research are. The results of this study are 1. Utilization of Nagari Assets in Nagari Tanjuang Bonai, Tanah Datar Regency, such as a. fixed asset utilization activities, b. utilization activities by administering fixed assets, and c. Nagari asset utilization activities by applying fixed asset reporting.